2018
DOI: 10.3390/d10020039
|View full text |Cite
|
Sign up to set email alerts
|

Land Manager Perspectives on Conflict Mitigation Strategies for Urban Flying-Fox Camps

Abstract: Abstract:Over the last 20 years, there has been a notable increase in the presence of flying-foxes (Pteropodidae) in urban areas in Australia. Flying-foxes congregate during the day in camps which at times may contain many thousands of individuals. The associated noise, smell, mess and concerns about disease transmission can result in significant conflict with local communities. Managers of flying-fox camps use a range of management approaches to mitigate tensions, but the success or otherwise of these has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Flying fox’s ( P. giganteus ) foraging activities can damage a wide variety of fruit crops, often causing considerable economic losses, which exacerbates conflicts (Aziz et al 2017). The noise and smell from bat colonies, as well as concerns about disease transmission (e.g., Nipah virus), often result in conflicts with humans (Currey et al 2018). These human–wildlife conflicts may shape the distribution of flying fox populations in urban and rural areas (Aziz et al 2017, Currey et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flying fox’s ( P. giganteus ) foraging activities can damage a wide variety of fruit crops, often causing considerable economic losses, which exacerbates conflicts (Aziz et al 2017). The noise and smell from bat colonies, as well as concerns about disease transmission (e.g., Nipah virus), often result in conflicts with humans (Currey et al 2018). These human–wildlife conflicts may shape the distribution of flying fox populations in urban and rural areas (Aziz et al 2017, Currey et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The noise and smell from bat colonies, as well as concerns about disease transmission (e.g., Nipah virus), often result in conflicts with humans (Currey et al 2018). These human–wildlife conflicts may shape the distribution of flying fox populations in urban and rural areas (Aziz et al 2017, Currey et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Hall 2002;Roberts 2006;Kung et al 2015). The management of these issues requires councils to find a balance between legal obligations, conservation of a threatened species and the needs of the community (Thiriet 2010;Holmes and Walker 2011;Currey et al 2018). This task is made more difficult by the inherent complexities and uncertainties involved, which are influenced by a range of biological, social, political and financial factors.…”
Section: Reflections On the Management Of The Kareela Flying-fox Campmentioning
confidence: 99%
“…Flying-foxes hold pest status among farmers and backyard fruit growers McClelland et al 2011), while the amenity values of urban communities are often incompatible with the presence of flying-fox camps (Roberts et al 2011). Residents and businesses may be negatively affected by the noise and smell generated by these camps, as well as the faeces and urine deposited by flying-foxes moving overhead (Currey et al 2018). These impacts are also compounded by fears of disease (Field 2018) and the emotions triggered by the sight of large congregations of flying-foxes based on complaints received by local councils (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Community-driven and unregulated culling and roost dispersal were the primary modes for managing conflict with flying-fox populations [36]. Despite the introduction and enforcement of protective legislation, current land management strategies for flying-foxes still focus on removing resources to deter the establishment of roosts near human settlements [37]. Experience has shown that relocating flying-fox camps is expensive and almost always fails in the longer term [11, 38].…”
Section: Introductionmentioning
confidence: 99%